PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWTOON KENALI HEWAN DISEKITAR KITA UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS III DI SD NEGERI PINGIT - Windi Dwi Pertiwi; Arip Febrianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop Powtoon-based learning media on the topic “Recognizing Animals Around Us” to improve the learning interest of third-grade students at SD Negeri Pingit Yogyakarta. The research used a Research and Development (R&D) method with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through expert validation questionnaires, teacher and student response questionnaires, and learning outcome tests (pretest and posttest). The results showed that the media was highly feasible, with media expert validation of 85% and material expert validation of 84.52%. Teacher responses reached 89.7% and student responses 96.88%, indicating that the media is practical and well-received. Learning activities also showed very good results with an average observation score of 90%, reflecting high student engagement and interest. Furthermore, student learning outcomes increased significantly, with the average score rising from 63.33 (pretest) to 89.76 (posttest). Statistical analysis using the Paired Sample t-Test showed a significance value of less than 0.05, indicating a significant difference between pretest and posttest results. Thus, Powtoon-based learning media is effective in improving both students’ learning interest and learning outcomes.